Higher fall rates and broader kinematic diversity in bilateral versus unilateral unconstrained slips - Abderrahman Ouattas; Andrew Walski; Seongwoo Mun; Corbin M. Rasmussen; Nikolaos Stergiou; Nathaniel H. Hunt (PLoS ONE, 2025)
Identifying and categorizing slip types by their risk level is essential for developing effective training protocols to prevent slip-induced falls. While previous research has thoroughly examined various slip types in sagittally constrained and unconstrained unilateral slips, little is known about the broader range of unconstrained unilateral or bilateral slips that closely mirror real-world conditions. In this study, we addressed three primary questions: (1) Do bilateral slips produce higher fall rates than unilateral slips? (2) Do bilateral slips exhibit greater slip diversity? (3) Does separating diverse slips by slip type reveal differences in severity, such as whole-body angular momentum and foot velocities? We administered three sudden, unconstrained unilateral or bilateral slips, using a wearable perturbation device, during over-ground walking to 20 younger adults (age: 27 ± 4.71 years in the unilateral group, 26.5 ± 4.03 years in the bilateral group), with whole-body kinematics and ground reaction forces recorded. Probabilistic Graphical Models assessed slip diversity and severity for each group, while multivariate general linear models examined whole-body angular momentum and average foot velocities after trailing leg touchdown across slip types. Six falls (21.42% fall rate) occurred in the bilateral slip group, whereas no falls were observed in the unilateral group, indicating that bilateral slips are more severe. Entropy analyses showed that bilateral slips had 21.44% greater outcome diversity compared to unilateral slips. We identified three slip types, high, medium, and low severity, based on frontal and sagittal foot movements following trailing foot touchdown. These categories differed significantly in whole-body angular momentum and foot velocities, suggesting distinct severities and underlying biomechanics. Future studies should examine whether different slip contexts (unilateral vs. bilateral) and slip types demand unique coordination strategies for fall prevention.